2017
DOI: 10.14202/vetworld.2017.738-742
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of pathogenic Pseudomonas aeruginosa from bovine subclinical mastitis in West Bengal, India

Abstract: Aim:Subclinical mastitis in bovines is mainly responsible for the huge economic loss of the dairy farmers, of which Pseudomonas aeruginosa is one of the causative agents. The study was aimed at a screening of suspected milk samples from different cattle farms of West Bengal for detection and confirmation of P. aeruginosa strains followed by their characterization.Materials and Methods:Around 422 milk samples were screened from different dairy farms primarily by on-spot bromothymol blue (BTB) test and then in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…P. aeruginosa is one of the more common conditional pathogens in the clinic and is also a common bacterial infection in wounds. A literature search showed that P. aeruginosa has been isolated from mastitis tissues of bovines and caprines (Banerjee et al, 2017;Scaccabarozzi et al, 2015), but there are few reports of this pathogen infection in human mastitis. P. stutzeri is a Gramnegative, rod-shaped, aerobic, catalase-and oxidase-positive bacterium that is ubiquitously present in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa is one of the more common conditional pathogens in the clinic and is also a common bacterial infection in wounds. A literature search showed that P. aeruginosa has been isolated from mastitis tissues of bovines and caprines (Banerjee et al, 2017;Scaccabarozzi et al, 2015), but there are few reports of this pathogen infection in human mastitis. P. stutzeri is a Gramnegative, rod-shaped, aerobic, catalase-and oxidase-positive bacterium that is ubiquitously present in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is an effective antibiotic agent against bovine mastitis which is primarily caused by bacteria (Saidi et al, 2019) (Ruegg, 2017). In India, mastitis causes major annual economic losses (Banerjee et al, 2017). Antibiotics are highly soluble in water and are the least usable biologically.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of virulence factors contribute to the pathogenicity of P.aeruginosa and are targeted by PCR for its detection such as oprL gene and exoS gene (6), gyrB gene (2,7), ecfX genes (8), Quorum sensing gene (9), gene encoded to phospholipase (plcH), rhamnolipid AB (rhlAB), alkaline protease (aprA) and elastase (lasB) (10) beside exotoxin A (ETA gene) (11,12). ETA gene is species specific and conserved for P.aeruginosa species and is not present in other species of Psuedomonas genus.…”
Section: Introductionmentioning
confidence: 99%